2012
DOI: 10.1134/s1070363212020211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1H-pyrazolo[3,4-c]isoquinolin-1-ones by the condensation of cyclohexanone derivatives with 3-amino-1-phenyl-1H-pyrazol-5(4H)-one

Abstract: The synthesis of 1H-pyrazolo[3,4-c]isoquinolin-1-ones was carried out by reacting 3-aryl(heteryl)-2,4-diacetyl-5-hydroxy-5-methylcyclohexanones with 3-amino-1-phenyl-1H-pyrazol-5(4H)-one. The structure of the 7-acetyl-2, 4,6,7,8,9-hexahydro-8-hydroxy-5,8-dimethyl-2-phenyl-6-(fur-2-yl)-1H-pyrazolo[3,4-c]isoquinolin-1-one obtained was proved by X-ray diffraction analysis.On the basis of tetrahydroisoquinoline a series of compounds used in medicine as drugs has been synthesized [1, 2]. Besides, the isoquinoline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…IR spectrum, ν, cm -1 : 3392 (OH), 1709 (C=O). 1 The IR spectra were recorded in KBr on a Perkin Elmer Spectrum One spectrometer. The 1 H and 13 C NMR spectra were measured on a Bruker Avance instrument at 399.95 and 100 MHz, respectively, using DMSO-d 6 as solvent and tetramethylsilane as internal reference.…”
Section: -Alkylpyrazolo[34-c]mentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectrum, ν, cm -1 : 3392 (OH), 1709 (C=O). 1 The IR spectra were recorded in KBr on a Perkin Elmer Spectrum One spectrometer. The 1 H and 13 C NMR spectra were measured on a Bruker Avance instrument at 399.95 and 100 MHz, respectively, using DMSO-d 6 as solvent and tetramethylsilane as internal reference.…”
Section: -Alkylpyrazolo[34-c]mentioning
confidence: 99%
“…According to the X-ray diffraction data [1], molecules 1a and 1b in crystal are largely contributed by zwitterionic structure A. Compounds 1a and 1b in DMF in the presence of aqueous potassium hydroxide are likely to generate anion B which exists in tautomeric equilibrium with oxygen-centered anion C. The reaction of anion B with alkyl halides 2a and 2b yields N-alkylpyrazolo [3,4-c]isoquinolines 3a-3c.…”
mentioning
confidence: 99%
“…1,2 Also, monocyclic pyrazoles are useful scaffolds for the synthesis of larger fused heterocyclic systems. Among them, we can mention pyrazolo-fused pyrimidines, 3 quinolines, 4 pyridines, 5 thiazoles, 6 isoquinolines, 7 imidazoles, 8 diazepines, 9 and triazines. 10 Fused pyrazoles are important classes of heterocycles with effective biological activity such as antitumor, 11 antioxidant, 2 antimicrobial, 12 antiviral, 13 and as immunostimulatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterocyclization reactions of β-cycloketols are not well studied. Thus, the literature describes the preparation of isoquinolines 2 [3][4][5][6][7], indazoles 3 [8][9][10], benzo[c]isoxazoles 4 [9,10], [1,2,4]triazolo [3-b]quinazolines 5 [11] and pyrazolo[3-c]isoquinolines 6 [12] (Scheme 1) by reactions of beta-cycloketols with various 1,2-and 1,3-dinucleophilic agents. Despite the large attention paid to reactions of aminoazoles with 1,3-dielectrophilic agents (see reviews [13,14]), only a few examples of reactions involving β-cycloketols were found in the literature.…”
mentioning
confidence: 99%